Employing the model of analyze of variance in the study of regional tourism development in the Black Sea countries - Gabriela Stanciulescu; Emilia Titan (European Regional Science Association (ERSA), 2002)
All efforts to be made as to analyze the tourism activity on the Black Sea countries are justified by the tremendous potential due to the natural and cultural resources that are largely miscellaneous and of high quality. Those features turn the Romania, Bulgaria, Ukraine, Georgia and Turkey into attractive destinations for tourists. The main problem that occurs refers to the fact that the existence of some resources is not reason enough to make tourists choose such destinations. The system of the tourism statistic indicators has the purpose to characterize quantitatively and qualitatively, the process of the tourist activity and the causal relation between the factors that influence it. One of the main functions of the tourism indicators system is the characterization of the economic relation of Black Sea countries with other countries, of the efficiency of the cooperation relations in the frame of the international tourism relations. An attempt to draw up a coherent effective strategy for developing the regional tourism in the region of Black Sea in accordance with the market economy must begin with a realistic evaluation and analysis of the actual state of the tourism in the region and must have a starting point in a comparative analysis with the neighbourhood, from central and eastern Europe. A model of bifactorial variance analysis with regard to the issue of international tourism development in these countries is important for the economic and social policy, by sustaining the hypotheses about the existence of differences in average number of nights spent by foreign tourists in hotels and similar establishments between countries. This study aims at performing such evaluation using the data offered by the CESTAT Statistical Bulletin and the indicator selection and interpretation have taken into account the facilities of the actual information system. Thus, for such an analysis, data are depicted in a bidimensional matrix with r x s size and with xij elements which describe the average number of nights spend by foreign tourists in hotels and similar establishments, when one factor is on level i, i= (countries) and another on level j, j= (years). On the one hand, we analyze whether the differences recorded over the mentioned countries in the average number of night spend in hotels have statistic significance or not. In the other hand, we study whether the differences recorded over the years have statistic significance. A research into this issue can use the absolute total number of overnight stays of foreign tourists, but in order to ensure comparability of data and because there are differences between countries in number of bed-places, we proceed to turn absolute total figures in average figures. After computation for four years (1997-2000), for the countries: Czech Republic, Hungary, Poland, Romania, Republic of Slovenia and Slovak Republic and for a type I error probability a=0.05, we find the values for Fisher-Snedecor test for statistic significance of the differences between countries: Fr-1;(r-1)(s-1)=F5;15=71.776>Ftab 0.05;5;15=4.62 and between years: Fs-1;(r-11)(s-1)=F3;15=0.02<Ftab 0.05;3;15=8.70 So, the result confirm the hypotheses of significant differences (p<0.05) between counties in central and eastern Europe in average number of nights spend by foreign tourists in hotels. In a Post-hoc comparison of means with Scheffe test we found that there are significant differences between Poland and Romania (on the one hand) and almost all the other countries, in the other hand: in Poland and Romania, the average number of nights spend in hotels by foreign tourists is smaller.
Keywords: 330